2021
DOI: 10.1159/000519010
|View full text |Cite
|
Sign up to set email alerts
|

Zuogui Pill Attenuates Neuroinflammation and Improves Cognitive Function in Cerebral Ischemia Reperfusion-Injured Rats

Abstract: <b><i>Introduction:</i></b> Cerebral ischemia and reperfusion (CI/R) injury is a devasting cerebrovascular disease, accompanied with ischemia stroke, cerebral infarction. Zuogui Pill (ZGP), as a Chinese traditional medicine, is proved to be effective in many diseases and cancers. Our study aimed to detect the roles of ZGP in CI/R injury. <b><i>Methods:</i></b> Neural stem cells were isolated from rats and induced by oxygen and glucose deprivation and recovery. CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Our in vitro experiments in this study demonstrated that ZGP protected ischemic neurons by increasing the cell viability of differentiated SH-SY5Y cells following OGD/R. Several other investigations have revealed that the mechanism behind ZGP’s protective impact on ischemic stroke is related to inhibit oxidative stress and inflammatory reaction and regulate PI3K/Akt pathway ( Liu et al, 2017 ; Liu et al, 2021 ; Liu et al, 2022 ). However, the effect and mechanism of ZGP on neurite growth and regeneration have not been experimentally verified.…”
Section: Discussionsupporting
confidence: 53%
“…Our in vitro experiments in this study demonstrated that ZGP protected ischemic neurons by increasing the cell viability of differentiated SH-SY5Y cells following OGD/R. Several other investigations have revealed that the mechanism behind ZGP’s protective impact on ischemic stroke is related to inhibit oxidative stress and inflammatory reaction and regulate PI3K/Akt pathway ( Liu et al, 2017 ; Liu et al, 2021 ; Liu et al, 2022 ). However, the effect and mechanism of ZGP on neurite growth and regeneration have not been experimentally verified.…”
Section: Discussionsupporting
confidence: 53%
“…Cerebral ischemia alters cerebrovascular hemodynamics, thus affecting oxygen and nutrient supply to the brain, with profound implications for nervous system function [62]. This impairment transcends cognitive and motor functions, extending into the modulation and stage of sleep [63,64]. Recent studies highlighted the intricate link amongst cerebral ischemia, cerebrovascular hemodynamics and sleep [65,66].…”
Section: Cerebral Vascular Hemodynamicsmentioning
confidence: 99%